Ideologi-structural analysis of external influences on current human rights discourses in Malaysia. - Lopez C., Carolina (Universiti Kebangsaan Malaysia, 2001)
In Malaysia the government of Prime Minester Dr. Mahathir Mohamad and members of the country's opposition are currently engaged in a lively debate concerning basic human rights (HR). Major players in the contestation of the State's HR policies are political leaders and Reformasi activists, as well as several HR-oriented NGOs. The present paper aims to present an analytical tool-the Ideological-Structural Analysis-which asks questions concerning the nature of culture, values, belief systems and the underlying ideology binding human societies together. Having examined the nature of cultural communities, it then attempts to assess how and to what extent outside human rights discourses might serve as a catalyst for current activism found in Malaysia.